Threshold effect of plasma total homocysteine levels on cognitive function among hypertensive patients in China: A cross-sectional study - Wang, Li; Chen, Jianduan; Li, Junpei; Hu, Feng; Xie, Yanyou; Zhou, Xinlei; Shen, Si; Zhou, Wei; Zhu, Lingjuan; Wang, Tao; Tu, Jianglong; Bao, Huihui; et al. (Frontiers in Neurology, 2022)
Abstract Background：Increased plasma total homocysteine (tHcy) is an influencing factor of cognitive impairment in the general population. However, studies on the relationship between the risk of cognitive impairment and plasma tHcy levels in patients with hypertension are limited. This study aimed to explore the association between plasma tHcy levels and cognitive function assessed by MMSE scores among hypertensive patients in China. Methods: A total of 9527 subjects from the Chinese Hypertension Registry Study participated in this study. Plasma tHcy levels were quantified by high-performance liquid chromatography using a fluorescence detector. Cognitive assessment was performed using the Mini-Mental State Examination (MMSE). Linear regression models, two piecewise linear regression models and smoothing curve fitting were applied to determine the relationship between plasma tHcy levels and cognitive function. Results: This analysis included 9527 Chinese hypertensive adults. Based on the results of linear regression models, a negative relationship was identified between between plasma tHcy levels and MMSE scores [ beta coefficient (β) per standard deviation (SD) increase: -0.26, 95% confidence interval (CI) -0.35, -0.16, P <0.001]. The fully adjusted smooth curve fitting presented a nonlinear between plasma tHcy levels and MMSE scores. The threshold effect analysis showed that the inflection point of tHcy was about 27.1 μmol/L. The effect size [β (95% CI)] per SD increase in plasma tHcy concentrations on MMSE scores was -0.93 (-1.24, -0.6) on the left side and -0.07 (-0.24, 0.10) on the right side of the inflection point (P-value for log-likelihood ratio (LLR) test was less than 0.001). Moreover, subgroup analyses revealed that sex could influence the negative association between plasma tHcy levels and MMSE scores up to a specific threshold (P-value for interaction <0.001). Linear regression models indicated that there was an enhanced inverse association between tHcy levels and MMSE scores in female with tHcy concentrations less than 26.9 μmol/L compared to male with tHcy concentrations less than 32.0 μmol/L. Conclusions: Plasma tHcy levels had a threshold effect on MMSE scores among hypertensive patients in China. Increased plasma tHcy levels were independently inversely associated with cognitive decline among hypertensive patients with tHcy concentrations less than 27.1 μmol/L.